Profil Lendir Serviks Rusa Timor (Cervus Timorensis) Betina Yang Mendapat Suplementasi Mineral Pada Tiap Fase Berahi - W. Purwaningsih; D. Samsudewa; Y.S. Ondho (Jurnal Sain Peternakan Indonesia, 2018)
The aims of this research were to observed the effect of zinc (Zn), magnesium (Mg) and selenium (Se) to the abundance, color and spinnbarkeit of cervical mucus. The materials used 10 Timor deer with BCS (Body Condition Score) 2-3,25, poel 2 and had different estrous phase. The parameters were observed the abundance, color and spinnbarkeit of cervical mucus. The data of abundance and color of cervical mucus were analyzed by Mann Whitney U-test and the data of spinnbarkeit were analyzed by t-test. The treatments were zinc (Zn), selenium (Se) and magnesium (Mg) supplementation (T1) on mineral block form and control (T0). The results showed that Zn, Se, and Mg supplementation had no significant effect (P>0,05) to the abundance, color and spinnbarkeit of cervical mucus Timor deer on estrous phase. It was caused by the high zinc level on feed, so the cervical mucus profile had no difference between T0 and T1.Key words : Mineral Supplementation, Cervical Mucus, Timor Deer